Justice for the Rights of the Women's Heirs to the Land of Dati - Latupono, Barzah; Radjawane, Pieter; Laturette, Adonia Ivone (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Maluku Province has a patrilineal customary law community, whose blood ties follow the father's line. The rights and obligations of the child are determined by the father and his relatives.Purposes of the Research: The research was conducted using an empirical juridical approach, which is a descriptive study of qualitative analysis.Methods of the Research: This research tries to describe the justice for the female heirs over the land of the dati in Leihitu, Central Maluku district. The results of collecting, finding data and information through a literature study on the assumptions used in answering the problems in this research, will be tested inductively-verificatively on the latest facts found in the community.Results of the Research: Boys have an important position in the family, while girls don't really benefit. In the distribution of land inheritance, women are not given full rights, because it is considered that women will marry and then leave with their husband's family. This reason is not to limit women's rights, nor is it because of following patrilineal kinship, but this is because during the Hongi Cruise the men take a long voyage with tough challenges, which a woman cannot do. Women in Leihitu, Central Maluku Regency, do not get inheritance rights, they only have the right to enjoy as long as they are not married. If they are married, then they do not have the right to enjoy it again, but they will have the right to enjoy dati in their husband's family